Human resource accounting and organizational productivity of listed manufacturing firms in Nigeria - Ogundajo, Grace Oyeyemi; Nwaobia, Appolos N; Uhuaba, Okezie; Phillips, Rhoda Temitope (International Journal of Emerging Trends in Social Sciences, 2023)
In many developing economies, studies have shown that meeting organizational productivity seems complex and characterized with several factors affecting the productive inputs, due to infrastructural deficits and extent of employees’ motivations capable of impeding productivity. Beyond these, adequate human resource accounting has been identified as a possible solution. However, the extent to which human resource accounting could impact on organizational productivity remains uncertain. Consequently, this study investigated the effect of human resource accounting on organizational productivity of listed manufacturing companies in Nigeria. An ex-post facto research design was employed, while from a population of 66, the study selected 20 manufacturing companies listed in Nigeria as of 31 December 2021, using purposive sampling technique. Data were extracted from the financial statements of the selected companies for a period of 15 years spanning from 2007 to 2021. Using panel data analysis, the study found that human resource accounting had a positive significant effect on organizational productivity of the listed manufacturing companies in Nigeria. Based on the results, the study recommended that managers should consider appropriate incentives capable of improving employees’ productivity and adopt adequate human resource accounting models to enhance organizational productivity.